Enabling African research item discoverability through the Research Nexus - (:unkn) unknown (My University, 2023)
We will hear about the Crossref Research Nexus and about the activities of the Crossref Ambassadors in Africa. Read more and watch the recording at https://africarxiv.pubpub.org/pub/wgadqkel/
Keywords: Crossref; Discoverability; Research Nexus; African research item